Effect of excess mgo mole ratio in a stoichiometric cordierite (2MgOÂ·2Al2O3Â·5SiO 2) composition on the phase transformation and crystallization behavior of magnesium aluminum silicate phases - Banjuraizah, Johar; Hasmaliza, Mohamad; Zainal Ariffin, Ahmad (The American Ceramic Society, 2011)
Link at publisher's homepage at http://onlinelibrary.wiley.com/